(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The current research aimed to verify the role of e-government in promoting sustainable development by reviewing some practices and a number of related studies. The study discovered that there are five e-government factors that have a clear role in promoting sustainable development, which are (the legal factor, the technological factor, the effectiveness of institutional organization, cooperation between digital technologies and resource management, and citizen satisfaction). To achieve the objective of the research, a main measurement tool was adopted by designing a questionnaire and distributing it to a sample of the General Traffic Directorate at the Ghazaliya registration site and the crown registration site in Baghdad - to reach the desired results through the use of the statistical package (SPSS.V.25) in order to determine the relationship between The variables of the study, e-government with its factors (the legal factor, the technological factor, the effectiveness of institutional organization, cooperation between digital technologies and resource management, citizen satisfaction). and sustainable development in its dimensions (environmental, social, and economic). The results of the study demonstrated the existence of an active role for e-government factors in sustainable development, and this indicates that these factors have a fundamental role in promoting sustainable development.